Legal and administrative aspects of environmental protection - Jabłoński, Maciej (Studia Ecologiae et Bioethicae, 2010)
Environmental protection is an area of interdisciplinary, in which the rule is the use of science concepts relevant to the legal, natural, technical or chemical. Therefore, in practice they may have different meanings depending on the conceptual context in which they are used. The concept, which draws attention to the rights and duties of citizens, public administration or environmental organizations, the legal and administrative aspects of environmental protection. Legal and administrative aspects of the environment in a manner related to the inherent rights of citizens, duties of public administrations, as well as practice and custom of our country and the European Union. Thus, their analysis is certainly an interdisciplinary context, and an important environmental dimension, the effect will be implied in the form of application by analogy comparisons and examples of not only national but international.